Agent Based Modeling for Estimating Energy-saving Potential of Offices Under Different Pricing Mechanisms. (May 2017) - Lin, Haiyang; Wang, Qinxing; Sun, Qie; Wennerstern, Ronald
Abstract: An agent-based model is developed to estimate the potential of energy savings of an office room under different pricing mechanisms. For this aim, an energy balance model was developed to simulate the operation of air conditioner operation, the heat flux of different behavior and the electricity consumption of different types of appliances according different energy consumption patterns was investigated in detail. The total electricity consumption reduced 3.9%-17.1% under different pricing mechanisms. Light's energy saving potential is the biggest among the electric appliances. The maximum-saving behavior is investigated and the total energy saving potential of it is 26.91%.